Parent Training: Techniques for Preventing and Handling Bullying in Children - Devid Dwi Erwahyudin; Afitria Rizkiana; Dwi Estiningsih; Masitoh (International Journal Of Community Service, 2024)
This community service aims to empower parents in preventing and dealing with bullying in children. The specific goals of this program are to increase parents' knowledge about bullying, develop effective communication skills, and build a supportive family environment. The hypothesis put forward is that the training provided will increase parents' knowledge and skills in recognizing and handling bullying cases, as well as reducing bullying incidents among children. The methods used include lectures to convey basic material about bullying, group discussions to share experiences and handling strategies, as well as case simulations for direct practice in handling bullying. Evaluation is carried out through pre-test and post-test to assess the increase in participants' knowledge and skills. The expected result is an increase in parents' awareness and ability to prevent and deal with bullying, as well as the creation of a safer and more supportive environment for children. It is hoped that this training can contribute to comprehensive bullying prevention efforts and strengthen the role of parents in supporting children's welfare.